Validity of long-term and short-term recall of occupational sitting time in Finnish and Chinese office workers - Ying Gao; Neil J. Cronin; Nina Nevala; Taija Finni (Elsevier, 2020)
Background: As sedentary behavior is a global health issue, there is a need for methods of self-reported sitting assessment. The accuracy and reliability of these methods should also be tested in various populations and different cultural contexts. This study examined the validity of long-term and short-term recall of occupational sitting time in Finnish and Chinese subgroups. Methods: Two cohort groups of office-based workers (58.6% female, age range 22-67 years) participated: a Finnish group (FIN, n = 34) and a Chinese group (CHI, n = 36). Long-term (past 3-month sitting) and short-term (daily sitting assessed on 5 consecutive days) single-item measures were used to assess self-reported occupational sitting time. Values from each participant were compared to objectively measured occupational sitting time assessed via thigh-mounted accelerometers, with Spearman's rho (ρ) used to assess validity and the Bland-Altman method used to evaluate agreement. Coefficients of variation depicted day-to-day variability of time spent on sitting at work. Results: In the total study sample, the results showed that both long-term and short-term recall correlated with accelerometer-derived sitting time (ρ = 0.532, 95% confidence intervals (CI): 0.336-0.684, p< 0.001; ρ = 0.533, 95%CI: 0.449-0.607, p< 0.001, respectively). Compared to objectively measured sitting time, self-reported occupational sitting time was 2.4% (95%CI: −0.5% to 5.3%, p = 0.091) and 2.2% (95%CI: 0.7%-3.6%, p = 0.005) greater for long-term and short-term recall, respectively. The agreement level was within the range −21.2% to 25.9% for long-term recall, and −24.2% to 28.5% for short-term recall. During a 5-day work week, day-to-day variation of sitting time was 9.4% ± 11.4% according to short-term recall and 10.4% ± 8.4% according to accelerometry-derived occupational sitting time. Conclusion: Overall, both long-term and short-term self-reported instruments provide acceptable measures of occupational sitting time in an office-based workplace, but their utility at the individual level is limited due to large variability.